Pengaruh Ramadan Atmosphere terhadap Impulse Buying dan Customer Satisfaction dengan Family Orientation Sebagai Mediator pada Pembeli Pasar Ramadan 1447 H di Tanah Grogot - Ibnu Khayath Farisanu; Ainun Ainun; Nadya Herma Salsabila (Journal of Management and Creative Business, 2026)
This study investigates the influence of Ramadan Atmosphere on Impulse buying and Customer Satisfaction, with Family orientation serving as a mediating variable, among shoppers at Ramadan 1447 H markets in Tanah Grogot, Paser Regency, East Kalimantan Province, Indonesia. Grounded in the Stimulus-Organism-Response (S-O-R) framework, the study conceptualizes Ramadan Atmosphere as the environmental stimulus (S), Family orientation as the internal organismic state (O), and Impulse buying and Customer satisfaction as behavioral responses (R). A quantitative cross-sectional survey design was employed, collecting data from 385 respondents across three Ramadan market locations during Ramadan 1447 H / March 2026. Partial Least Squares Structural Equation Modeling (PLS-SEM) with bootstrapping (5,000 subsamples) was used for hypothesis testing. All seven hypothesized paths were supported at p < 0.001. Ramadan Atmosphere exerted a strong direct effect on Family orientation (β = 0.497), and significant direct effects on both Impulse buying (β = 0.319) and Customer satisfaction (β = 0.314). Family orientation significantly predicted Impulse buying (β = 0.357) and Customer satisfaction (β = 0.330), and partially mediated both relationships (indirect effects: β = 0.178 and β = 0.164, respectively). The model explained 30.0% of variance in Impulse buying and 32.5% in Customer Satisfaction. These findings contribute to retail atmospherics theory by operationalizing Ramadan Atmosphere as a measurable, culturally-embedded construct and by demonstrating that the collective values dimension, particularly family orientation, constitutes a critical psychological mechanism through which seasonal religious stimuli generate consumer behavioral responses in collectivist Muslim societies.